Budget Optimization for Managerial Performance Achievement - Adiani, Dillah Rezki; Dali, Nasrullah; Nurdin, Emillia (Dinasti Publisher, 2026)
This study aims to explore the role of budget participation in enhancing managerial performance through a qualitative approach based on a scoping review. The background of this research is rooted in the importance of involving managers in the budgeting process as a key instrument for effective resource management in public sector organizations. The data were obtained from journal articles published between 2020 and 2024, accessed via Google Scholar using the Publish or Perish (POP) software. A purposive sampling technique was employed, with inclusion criteria focusing on articles that addressed the variables of budget participation and managerial performance. The findings indicate that budget participation positively influences managerial performance, particularly when supported by organizational commitment, effective leadership, and robust internal control systems. Budget participation facilitates dialogue between managers and superiors, enhances ownership of organizational goals, and strengthens accountability. However, the effectiveness of participation is not universal and depends on the organizational context and structural support. This study contributes theoretically to the field of public sector accounting and offers practical insights for improving budget management quality in local governments.